Pan-African granulites of Madagascar and southern India: Gondwana assembly and parallels with modern Tibet - Fitzsimons, Ian (Japan Association of Mineralogical Sciences, 2016)
Granulites of the southern East African Orogen formed by continental collision during Gondwana assembly. The highest metamorphic gradients of 25-50°C km-1 were attained at 0.58-0.53 Ga in a microcontinental block that was sandwiched between two collisional sutures and is now exposed in Madagascar and southern India. The 50 Myr duration of extreme pressure-temperature (P-T) conditions and lack of coeval mantle magmatism suggest that metamorphism was driven by radiogenic heat accumulation beneath a long-lived orogenic plateau. Bounding sutures most likely record transfer of this microcontinent across the Neoproterozoic Mozambique Ocean, analogous to Gondwanan terranes that crossed Tethys before final India-Asia collision and, like Tibet, these sutures mark the edges of a plateau that formed following terminal ocean closure and collision. Both sutures record moderate metamorphic gradients of 15-25°C km-1 but with quite different ages. Metamorphism along the western suture at 0.65-0.61 Ga followed the end of magmatism in an adjacent 0.85-0.65 Ga ocean-arc terrane. It has an anti-clockwise P-T path that reflects preferential thickening of the hot arc during early stages of collision, and dates ocean closure at the western suture. Metamorphism along the eastern suture at 0.53-0.51 Ga has a clockwise P-T path and is widely assumed to date terminal collision in the East African Orogen. However, this event was coeval with rapid exhumation of granulites in the adjacent plateau and is more likely to reflect reactivation of a much older eastern suture during plateau collapse. Great care should be taken when using metamorphism to date ocean closure in ancient orogens. Rocks with hot metamorphic gradients give poor age constraints on initial collision because peak T is attained >50 Myr after ocean closure if radioactivity is a major part of the heat budget. Suture zone rocks with moderate metamorphic gradients can provide more reliable estimates for the time of ocean closure but are also prone to later reactivation in orogens with protracted histories.